Effectiveness of heart failure management programmes with nurse-led discharge planning in reducing re-admissions: A systematic review and meta-analysis - Kalogirou, Fotini; Lamnisos, Demetris; Sourtzi, Panayota A.; Lambrinou, Ekaterini (My University, 2012)
Background: Heart failure (HF) is a clinical condition with major socioeconomic burden. Scientists are trying to find effective solutions to eliminate the effects of the disease and the current innovations in research address the introduction of HF management programmes (HF-MPs). Objectives: A meta-analysis was undertaken to estimate the effect of HF-MP with a nurse-driven pre-discharge phase on the outcomes of HF and all-cause re-admission. Data sources: A systematic search of PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Cochrane Library (reviews and clinical trials) was performed to locate randomised controlled trials (RCTs), published in English language, which implemented any HF-MP with discharge planning carried out by a nurse. Identified articles were further screened for additional studies. Study selection: Two reviewers independently screened relevant abstracts or titles using a standardised predefined check list. Pilot studies, studies additionally assessing other conditions and studies that evolved technology utilities or included medication management beyond optimisation of therapy, were excluded. Data extraction: Selected articles were thoroughly screened and data of interest (characteristics and outcomes) were obtained. Quality assessment was done by two reviewers separately. Data synthesis: Nineteen RCTs were selected for the meta-analysis. The overall pooled effect (relative risk, RR) of the intervention group compared with the control group was estimated by using a random effects analysis (95% confidence interval (CI)) for the outcomes of HF-related re-admission and all-cause re-admission. The overall RR of HF re-admissions was 0.68, 95% CI (0.53, 0.86), . p<. 0.05 and of all-cause re-admission was 0.85, 95% CI (0.76, 0.94), . p<. 0.05 favouring the intervention. Metaregression analysis was performed while trying to explain the observed heterogeneity but none of the factors (environment, duration of follow-up, origin and complexity) were significantly related with the RR.No significant publication bias was observed regarding both HF and all-cause re-admission. Conclusions: The results of the current meta-analysis highlight the potential of HF-MPs with nurse-driven pre-discharge interventions to reduce hospital re-admissions. Essential characteristics or components of a successful HF-MP are still to be determined, thus more studies are required to solve this issue. 2011 Elsevier Ltd.
Keywords: Heart failure; Hospital discharge; Meta analysis; Nurse; Nursing; Heart Failure; Humans; Patient Discharge